Research on the Relationship between Leadership Skills and Participation in Extracurricular Sports Activities among Junior High School Students in Hainan, China - Wang, Jing; Ismail, Aziah (Journal of Ecohumanism, 2024)
This research explores the relationship between leadership skills and participation in extracurricular sports activities among junior high school students in Hainan, China. The study aims to investigate how engagement in sports activities outside of the regular curriculum contributes to the development of leadership qualities such as communication, teamwork, decision-making, and problem-solving. A quantitative approach was employed, the surveys with 512 students to gather quantitative data. The findings indicate a significant positive correlation between active involvement in extracurricular sports and the enhancement of leadership skills, with students demonstrating improved confidence, responsibility, and social cohesion. These results suggest that participation in sports plays a critical role in fostering leadership abilities at a formative age, providing valuable insights for educators and policymakers to promote well-rounded student development through extracurricular programs. The study also highlights potential cultural and regional factors unique to Hainan that may influence the dynamics of leadership and sports participation. The research highlights the important role of extracurricular sports in developing leadership skills among junior high school students in Hainan, China. It suggests that schools and policymakers should prioritize sports programs, as they contribute to key leadership traits like teamwork, communication, and problem-solving. These activities not only enhance physical health but also foster personal growth, including confidence and responsibility. The study emphasizes the value of designing sports programs that actively promote leadership development and the importance of considering cultural and regional factors. Additionally, it encourages further research on the long-term impact of sports participation on leadership and its transfer to academic and career success.